2020
DOI: 10.3390/s20195526
|View full text |Cite
|
Sign up to set email alerts
|

Research on Temperature Variation during Coal and Gas Outbursts: Implications for Outburst Prediction in Coal Mines

Abstract: Coal and gas outbursts are among the most severe disasters threatening the safety of coal mines around the world. They are dynamic phenomena characterized by large quantities of coal and gas ejected from working faces within a short time. Numerous researchers have conducted studies on outburst prediction, and a variety of indices have been developed to this end. However, these indices are usually empirical or based on local experience, and the accurate prediction of outbursts is not feasible due to the complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Although deep coal and gas outbursts are intuitively closely related to the mining depth, they actually occur because the mining environment significantly changes with the increase in mining depth. In the deep mining environment, nonlinear changes in single vital indexes, such as the coal seam gas pressure, gas content, initial gas release velocity of coal, and coal firmness coefficient, are aggravated, and the degree of interaction between indexes increases, significantly aggravating the risk of deep coal and gas outbursts [37].…”
Section: Mining Depthmentioning
confidence: 99%
“…Although deep coal and gas outbursts are intuitively closely related to the mining depth, they actually occur because the mining environment significantly changes with the increase in mining depth. In the deep mining environment, nonlinear changes in single vital indexes, such as the coal seam gas pressure, gas content, initial gas release velocity of coal, and coal firmness coefficient, are aggravated, and the degree of interaction between indexes increases, significantly aggravating the risk of deep coal and gas outbursts [37].…”
Section: Mining Depthmentioning
confidence: 99%
“…Song and Zhang [27,28] predicted and visualized the coal-gas outburst area based on geographical information system technology. Zhang et al [29][30][31] studied a new prediction method of coal-gas outburst based on the η parameter that was put forward on the basis of experimental study, and its dangerous level was divided into five categories; the method was compared with other traditional methods at the same time. Liu et al's physical simulation system for large coal-gas outburst had been developed, and the occurrence mechanism of coal-gas outburst was analyzed from the perspective of energy, which laid a theoretical foundation for the accurate prediction of coal-gas outburst disasters.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 This change is more obvious especially in the case of coal and gas outburst. 16 When the temperature of the coal seam rises, the adsorption capacity of CBM changes. 17,18 Killingley and co-workers 19 showed that the methane adsorption capacity decreased by 0.12 cm 3 /g when the temperature increased by 1 °C at 5 MPa.…”
Section: Introductionmentioning
confidence: 99%